Zein as a renewable material for the preparation of green nanoparticles for drug delivery - Tivano, Francesca; Chiono, Valeria (Frontiers in Biomaterials Science, 2023)
Environmental sustainability is a key challenge driven by the increased consumption of natural resources with limited availability. In this scenario agriculture has emerged as a privileged source of renewable resources, hence more efforts should be addressed to the study of plant-derived materials for medical applications. Zein is a biocompatible, biodegradable and amphiphilic prolamin protein extracted from the endosperm tissue of corn. For these reasons, its applications span from coatings for edible capsules, to the fabrication of bi- and tridimensional scaffolds for tissue engineering, and to develop drug delivery systems. This review aims at describing the properties and main applications of zein with a focus on the most recent and updated state of the art literature on zein based nanoparticles for the controlled delivery of various drugs. The main focus is to analyze the state of the art literature to understand how to implement sustainable methods for the preparation of zein NPs and to propose their exploitation as novel drug delivery systems for multiple applications, including oligonucleotide delivery. Main methods for zein NP preparation are described under an ecofriendly point of view, highlighting their environmental sustainability based on used solvents, waste products and energy consumption.